Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Motivasi Terhadap Kinerja Guru (Studi Kasus pada Madrasah Aliyah Unggulan K.H. Abd. Wahab Hasbulloh) - Khotim Fadhli; Nurul Aminah; Lailatus Sa’adah (MAMEN: Jurnal Manajemen, 2023)
Teacher Performance is an outcome or achievement of a person or group in carrying out their work and responsibilities in accordance with their abilities in achieving goals. This research was conducted with the aim of determining the influence between leadership style, work environment, and motivation on teacher performance contained in the Madrasah Aliyah Unggulan K.H. Abd. Wahab Hasbulloh, Jombang Regency. In this study, the method used was a quantitative research method that displayed data in the form of numbers with calculations through SPSS software version 26 and used multiple linear regression analysis. In hypothesis testing using tests partially and simultaneously. The variables used in this study are free (independent) and bound (dependent) variables. The free variables are Leadership Style (X1), Work Environment (X2), and Motivation (X3), while the bound variables are Teacher Performance (Y). Based on data calculations using SPSS, the researcher obtained partial results that Leadership Style does not affect Teacher Performance, while Work Environment and Motivation affect Teacher Performance. The results obtained simultaneously between Leadership Style, Work Environment, and Motivation together have a significant influence on teacher performance. Keywords: Leadership Style, Work Environment, Motivation, and Teacher.